Effects of some pesticides on in vitro pollen germination and tube elongation of Malus sylvestris Miller (apple) and Prunus domestica L. (Pears) - Munzuroğlu, Ömer; Gür, Nazmi; Topdemir, Aykut (My University, 2013)
The toxicity of pesticides was investigated by determining the effect of selected pesticides on pollen germination of Mains sylveslris Miller (Apple) and Primus domestica L. (Pears), both in vitro. Among the pesticides tested, carbendazim and thiodan were much more toxic to apple and pears pollen germinated on Brewbaker-Kwack medium containing the test pesticides. Toxicity was greater when the pesticides were sprayed on the surface of germination medium. The fertilization of apple and pears were extremely sensitive to all pesticidal sprays when applied 2 hr before or 4 hr after hand pollination. Pollen tube growth and initial fruit set were influenced to a lesser degree when pesticides were applied to pollens on in-vitro germination.
Bildiri - Yayımlanmamış
Keywords: Pesticides; Effects; Pollen germination; Tube elongation; Malus Sylvestris Miller; Prunus domestica